Eppawala destruction of cultural heritage in the name of development - Mendis, D. L. O.; Sri Lanka Pugwash Group (Colombo : Sri Lanka Pugwash Group, 1999)
Effects of mining phosphate rock at Eppawala, Sri Lanka.
Keywords: Phosphate mines and mining -- Environmental aspects -- Sri Lanka -- Eppawala; Environmental policy -- Sri Lanka -- Eppawala